MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI ANALITIK MENGGUNAKAN MODEL CAFE - Trisnawati Trisnawati (Universitas Islam Negeri Mataram, 2022)
This research aimed to describe the implementation of cafe (critical thinking, active, fun, environment) model to enhance the students’ proficiency in writing analytical exposition texts The CAFE model was designed to make it easier for the students to write their analytical exposition texts by using three writing steps, pre-writing, writing, and post-writing activities. Some difficulties faced by students when they have to make a thesis, argue for it, and find evidence to support the arguments. The problem formulation of this research is how the CAFÉ learning model can enhance students’ ability to write analytical expository texts in XI IPA3 MAN IC Gorontalo. The method used in the research is Classroom Action Research with two cycles. Each cycle is conducted in three meetings. The respondents are 17 students in grade XI IPA3. The result shows that the average score in cycle one was 62.64, compared to 79.12 in cycle two. The CAFÉ model has proved that it can address the students’ difficulties in making their thesis, making arguments, finding evidence, connecting their ideas, and making a reiteration in writing analytical expository text.